EFEKTIVITAS MODEL RMS (READING, MIND MAPPING, AND SHARING) BERBANTUAN APLIKASI POWTOON DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS X IPS SMA NEGERI 1 LIRIK - Sri Yunita Ningsih; Helma Mustika; Nike Tiara Dita (Ensiklopedia Education Review, 2022)
The low ability of students' mathematical understanding, is influenced by the lack of interest of students in mathematics so that it eliminates the continuing curiosity. Then the students are less active in solving the questions given by the teacher. This study aims to determine the effectiveness of the RMS (Reading, Mind Mapping, and Sharing) model with the help of the Powtoon application in improving the mathematical understanding ability of students of class X IPS SMA Negeri 1 Lirik. This type of research is a Quasy Experiment Design research. The sampling technique is random sampling. After the samples were taken randomly, class X IPS 1 was chosen as the experimental class and X IPS 2 as the control class. The instrument in this research is a test of mathematical understanding ability. The data analysis technique used the Paired Samples T-Test (t test) by carrying out normality tests and homogeneity tests as prerequisite tests. The results of the hypothesis obtained a significance value = 0.000 and = 0.05. Because sig. < or 0.000 < 0.05, then accept H_1 and reject H_0. It was concluded that the RMS (Reading, Mind Mapping, and Sharing) model with the help of the Powtoon application was effective in improving the mathematical understanding ability of class X Social Studies students of SMA Negeri 1 Lirik.Keywords: RMS Learning Model, Powtoon Application, Mathematical Comprehension Ability.